Bortezomib in Anti-Cancer Activity: A Potential Drug - Rajagopal Appavu; Deepa Mohan (Global Journal of Cancer Therapy - Peertechz Publications, 2016)
26S proteasome is an intracellular; ATP dependent enzymatic complex degrades ubiquitin-tagged proteins and maintains cellular homeostasis. The orderly degraded proteins including cyclins, caspases, Bcl-xL, p53, cell adhesion molecules are involved in cell-cycle progression, tumor suppression, DNA replication, inflammation, and apoptosis. So, proteasome inhibition is a target therapy for cancer to promote cell cycle arrest or apoptosis. Bortezomib (Velcade®, PS-341, and Millennium Pharmaceuticals, Inc.) is the first, selective, reversible, and only proteasome inhibitor for the treatment of multiple myeloma have been approved by U.S. Food and Drug Administration (FDA) in 2003. Bortezomib downregulates the interaction of multiple myeloma cells with bone marrow stromal cells, inhibits angiogenesis, and blocks cell cycle progression. Clinically, continuous dosage of bortezomib leads to few side effects.